International Business - Agboveh, Maxwell (My University, 2009)
A firm is affected by various stakeholders in varying degrees. These stakeholders are located within the immediate operational and also external environment of the firm. The survival of the firm is highly dependent on the entire stakeholder constellation; the firm cannot survive in isolation. These stakeholders have various expectations in the firm which frequently conflict with the objectives of the firm. This study identifies the level of these conflicts and the strategies adopted by management in balancing such expectations. However, some researchers believe that conflicts are managed (Amason, 1996), others argue that conflicts are resolved (Wall and Callister, 1995). However, this study addresses the issue of ‘balancing’ conflicts. The study further attempts to probe what choices are available to management when faced with incongruent expectations from various stakeholder groups like increasing pressure on the firm from especially, the external environment (tertiary stakeholders). The study assumes that in spite of the perceived remoteness of these tertiary groups from the immediate boundaries of the firm, these stakeholder groups can cost the organization huge financial losses and bad publicity when their interests are underrated. Finally, pressure-response strategies that are adopted by management when confronted with organization-stakeholder conflicts are examined. Some of these strategies include: reactive, defensive, accommodative, problem-solving and proactive (Barki and Hariwick, 2001; Peng, 2006). Consideration is given to an alternative stakeholder model – tertiary stakeholders.
Keywords: Stakeholders; constellation; expectation; conflicts; balance; interest groups; tertiary stakeholders; fi=Master's Degree Programme in International Business|